PERCEPTIONS OF MEDICAL STUDENTS IN PREVENTING MEDICAL ERRORS AND PATIENT SAFETY: Medical Errors and Patient Safety - Khan, Najm-Us-Saqib; Qamar, Khadija; Sabir, Sohail (Pakistan Armed Forces Medical Journal, 2015)
Objective: To evaluate under graduate medical students’ perceptions on medical errors and patient safety.Study Design: Descriptive cross sectional study.Place and Duration of Study: Army Medical College from Dec 2014 to Jan 2015.Material and Methods: The  4x simulation role play patient safety sessions of 15 minutes each  took place in the lecture hall conducted on fourth-year medical students selected during a whole-class academic sessions in Dec 2014 and Jan 2015. Participants in these sessions were given clinical scenario after taking the informed written consent. After the role play, students were given the same questionnaire. Responses to each item were added using a like rt scale.Results: Most of the students agreed after the role play sessions that they had a good understanding of common medical errors.Conclusion: Medical students in Army Medical College had knowledge of medical errors as being a barrier between what is thought better and what is being available.